Clay‐Na as a sorbent for the extraction of anti‐inflammatory compounds in water samples. Issue 9 (21st March 2019) - Khazri, Hassen; Ghorbel‐Abid, Ibtissem; Ben Hassine, Sihem; Chevolleau, Sylvie; Debrauwer, Laurent; Kalfat, Rafik; Trabelsi‐Ayadi, Malika
Abstract: In this work, clay‐Na particles are used as the adsorbent for the solid‐phase extraction of acidic compounds. The novel sorbent under study is based on high‐specific surface area, cation‐exchange capacity designed specifically to offer ion‐exchange properties with the goal being to selectively extract a group of acidic compounds. The effects of the extraction parameters including extraction elution solvent, sample volume and pH. In optimum conditions, the repeatability for one fiber ( n  = 3), expressed as % relative standard deviation, was between 0.3 and 4.3% for the acid compounds. The detection limits for the studied acidic compounds were between 0.1–0.6 μg/L. The developed method offers the advantages of being simple to use and having a low cost of equipment.